A nucleation model associated with phase transitions in the indium-rich and Au-Cu-Zn alloys - Dogan, A (Czechoslovak Jnl of Physics, 1996)
This paper is concerned with the calculation of the critical radius and the wavelength of modulation associated with the strained inclusion during first order phase transition. For this purpose the forth order spatial gradient term was included into the free energy density inside the inclusion. Numerical results were obtained for indium-rich alloys such as In-21 at.% T1, In-4.4 at.% Cd and In-(13-X) at% Pb-X at.% Sn, and also the alloy Au-30 at.% Cu-47 at.% Zn. The effect of the temperature and the atomic fraction of alloying element on critical radius and wavelength of modulation is also discussed and compared to the experimental results.
Keywords: Martensitic-Transformation; Solid-Solutions; Thermodynamics; Zirconia; Energy